2012
DOI: 10.1016/j.ienj.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hospital pain management patterns and triage nurse documentation

Abstract: Unnecessary suffering may be avoided if the public had a better understanding of pain and the benefits of pain management. Further research is required to better understand the beliefs and attitudes towards pain and pain management by clinicians and the public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…If we are to improve the time to analgesia for this vulnerable ED patient group, nurse-initiated pain management policies and guidelines need to be revised to enable nurses to initiate and provide appropriate analgesics. We must improve pain management given that multiple studies (Fry et al, 2004;Arendts and Fry, 2006;Fry et al, 2011;2012), including this study, continue to identify an issue with the timely delivery of analgesia for older people, particularly for those with a cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…If we are to improve the time to analgesia for this vulnerable ED patient group, nurse-initiated pain management policies and guidelines need to be revised to enable nurses to initiate and provide appropriate analgesics. We must improve pain management given that multiple studies (Fry et al, 2004;Arendts and Fry, 2006;Fry et al, 2011;2012), including this study, continue to identify an issue with the timely delivery of analgesia for older people, particularly for those with a cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…To increase the understanding of how managers relate to a patient group, patients with acute abdominal pain (AAP) have been chosen since it is an internationally common patient group in acute care (Falch et al, 2014;Fry, Hearn, & McLaughlin, 2012). Studies have shown the need for improvements as these patients often report poor pain management, lack of information, and limited participation and engagement from health professionals that reduce the patients confidence in health care and can cause long-term consequences (Feo, Donnelly, Muntlin Athlin, & Jangland, 2019;Jangland, Kitson, & Muntlin Athlin, 2016;Muntlin Athlin, Carlsson, Safwenberg, & Gunningberg, 2011;Schultz, Qvist, Mogensen, & Pedersen, 2014).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…However, few studies have analysed caregiver–patient interactions on the issue of pain credibility, beside Baszanger's studies on pain medicine (Baszanger, , ) and Dodier's work on occupational medicine (Dodier, ). Specifically, in the ED context, there is a need of qualitative research to explore what are the beliefs and attitudes of triage nurses towards pain assessment tools and how they use them (Fry, Hearn, & McLaughlin, ).…”
Section: Introductionmentioning
confidence: 99%